High external quantum efficiency light-emitting diodes enabled by advanced heterostructures of type-II nanoplatelets - Durmusoglu, Emek Goksu (2023)
Colloidal quantum wells (CQWs), also known as nanoplatelets (NPLs), are exciting material systems for numerous photonic applications, including lasers and light-emitting diodes (LEDs). Although many successful type-I NPL-LEDs with high device performance have been demonstrated, type-II NPLs are not fully exploited for LED applications, even with alloyed type-II NPLs with enhanced optical properties. Here, we present the development of CdSe/CdTe/CdSe core/crown/crown (multi-crowned) type-II NPLs and systematic investigation of their optical properties, including their comparison with the traditional core/crown counterparts. Unlike traditional type-II NPLs such as CdSe/CdTe, CdTe/CdSe, and CdSe/CdSexTe1–x core/crown heterostructures, here the proposed advanced heterostructure reaps the benefits of having two type-II transition channels, resulting in a high quantum yield (QY) of 83% and a long fluorescence lifetime of 73.3 ns. These type-II transitions were confirmed experimentally by optical measurements and theoretically using electron and hole wave function modeling. Computational study shows that the multi-crowned NPLs provide a better-distributed hole wave function along the CdTe crown, while the electron wave function is delocalized in the CdSe core and CdSe crown layers. As a proof-of-concept demonstration, NPL-LEDs based on these multi-crowned NPLs were designed and fabricated with a record high external quantum efficiency (EQE) of 7.83% among type-II NPL-LEDs. These findings are expected to induce advanced designs of NPL heterostructures to reach a fascinating level of performance, especially in LEDs and lasers.